Conceptual Model of the Relationship Between Metacognitive Learning Strategies and Meta-Emotion with Academic Engagement Mediated by Attributional Styles in Students With High and Low Levels of Anxiety - Najafzade, Soroush; Jafar Tabatabaei, Toktam Sadat; Shahabizade , Fatemeh; Jarahi Friz, Jalil (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  The aim of this study was to examine a conceptual model of the relationship between metacognitive learning strategies and meta-emotion with academic engagement, mediated by attributional styles, in students with high and low levels of anxiety.Methods and Materials: This study employed a descriptive–correlational design using structural equation modeling and, in terms of purpose classification, was an applied research study. The statistical population included all upper secondary school students in Torbat-e Heydarieh during the 2023–2024 academic year (N = 12,713). Using G*Power software, a sample size of 372 students was determined, who were selected through multistage cluster sampling with proportional allocation by district. The research instruments included the Metacognitive Learning Strategies Questionnaire by Karimi (2002), the Meta-Emotion Scale by Mitmansgruber (2009), the Attributional Style Questionnaire (ASQ; 1982), and the Test Anxiety Questionnaire (TA; 1996).Findings: The results indicated that the model demonstrated adequate predictive power for the dependent variables at the 0.05 significance level. Subsequently, the model was analyzed using a factor analysis procedure in SmartPLS software. The findings showed that test anxiety did not have a significant moderating effect on the strength of the relationship between metacognitive learning strategies and academic engagement through the mediating role of attributional styles at the 0.05 significance level. In addition, test anxiety did not have a significant effect on the strength of the relationship between metacognitive learning strategies and meta-emotion with academic engagement through the mediating role of attributional styles at the 0.05 significance level.Conclusion: The final results indicated that through the design, instruction, and practice of using metacognitive strategies, meta-emotion, and attributional styles, students’ academic engagement increases; however, these factors do not have an effect on their test anxiety.